MOBILITAS KARIR DALAM ORGANISASI: IMPLIKASI DARI SISTEM KARIR DAN PERAN LEADERSHIP - Imronudin . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2003)
Career development in organization is an issue that getting more and more attention, both from academicians and practitioners. Career mobility in organization can't be separated from leadership role within, Moreover, career system applied in organization also has effect toward career mobility. Career mobility in an organization can be viewed either in individual context or organizational context. In an individual context, there are several factors affecting career mobility, such as social class; education and training; self-concept regarding career; career choice; family influence; age; gender; and race. At the same time, career mobility in an organizational context is affected by factors such as internal tabor market; career ladder; promotion; training and development; selection criteria and method; and internal competition.